Ativismo judicial no contexto das políticas públicas do direito à educação - Pereira Júnior, Valter Henrique (2020)
His paper seeks to analyze the practice of judicial activism of the Supreme Federal Court with regard to public educational policies of the human right to education between 2005 and 2020. This is a research with a predominantly qualitative approach and procedurally bibliographic and documentary. It stands out, the development of judicial activism as a worldwide phenomenon, characterizing its multiple dimensions in the Brazilian context, choosing to approach it according to institutional theory, in its political-institutional aspects, without disregarding the legal-normative aspects. It points to a concept of educational public policies, connected to the human right and fundamental to education, given that the latter as the object of disputes, suffers numerous influences in its content, meaning and contours, opening space for a performance of jurisprudential accommodation. It demonstrates how the judicial activism of the Brazilian Court is manifested in the educational public policies of the human right to education, as a basis its praxis of the Supreme Court taking into account dialogues elements with the other powers, social and political actors. We conclude that the activist practice of the Brazilian Court has contributed to the debate on the maintenance and expansion of public policies on the human right to education within the Brazilian institutional dynamics.